DEVELOPMENT OF EMOTIONAL INTELLIGENCE OF FUTURE PRIMARY SCHOOL TEACHERS - Moskalenko, Yuriy; Oliiar, Mariia (Mountain School of Ukrainian Carpaty, 2021)
The article analyzes the theoretical approaches to the development of scientifically sound methodological ways of teaching students majoring in "Primary Education" appropriate use of verbal means to emotionally and intellectually influence students in the process of learning. The importance of emotional intelligence of future primary school teachers in the context of their communicative activity is highlighted. Emphasis is placed on the importance of communicative training of students. It is noted that the achievement of a high level of speech culture of the teacher in terms of educational communication is manifested primarily in the appropriate use of verbal emotional and intellectual means, which are a manifestation of the emotional intelligence of the teacher. It is emphasized that the future teacher must take into account the psychological characteristics of children of primary school age in order to optimize educational communication, which is expressed in the emotional and intellectual features of the teacher's language behavior during pedagogical discourse. The essence of emotional intelligence is revealed in the Concept of the new Ukrainian school, which is characterized as a key competence necessary for successful self-realization of the individual in society. The basis of emotional intelligence are certain groups of cognitive, emotional, adaptive and social abilities that contribute to a positive climate in the team and prevent interpersonal conflicts. The specificity of emotional and intellectual manifestations in the teacher's activity is that it is an integral part of the teacher's language behavior, which demonstrates his individual style of activity and is aimed at activating the emotional and intellectual activity of students. To identify the level of understanding by future teachers of the meaning of the concept of "emotional intelligence" and its significance in the educational process of primary school, a survey of 80 third-year students majoring in "Primary Education" was performed and its results were described. The survey data of students showed that they are aware of the importance of the development of emotional intelligence for future successful professional activities, positively assess the importance of emotional teacher in the educational process of primary school. The ways of formation of emotional intelligence of future primary school teachers in the process of their professional training are revealed. It is noted that it is important in the course of professional training to enrich the arsenal of emotional means, rhetorical techniques of future teachers, to help them form an individual style of communicative behavior in various situations of pedagogical discourse, including its emotional and intellectual component.